Linear filtering with fractional Brownian motion in the signal and observation processes. (1999) - Kleptsyna, M. L.; Kloeden, P. E.; Anh, V. V.
Abstract : Integral equations for the mean-square estimate are obtained for the linear filtering problem, in which the noise generating the signal is a fractional Brownian motion with Hurst index h ∈ ( 3 / 4, 1 ) and the noise in the observation process includes a fractional Brownian motion as well as a Wiener process.